Toxocara canis Larval Migration Causing Verminous Pneumonia in Fading Puppies From 2 Scottish Terrier Litters. Issue 6 (November 2019) - Buckle, Kelly N.; Hardcastle, Michael R.; Scott, Ian; Craig, Linden E.; French, Adrienne; Gedye, Kristene; Collett, Mark Grey
Migration of vertically transmitted Toxocara canis larvae through the liver and lungs is poorly documented as a cause of periparturient mortality in puppies. This case series describes 4 cases of fading puppies in 2 litters from 2 different bitches owned by the same breeder. Of the 4 cases, 4 had verminous pneumonia, 2 had fibrinoid necrosis of pulmonary arterioles, 4 had hepatic necrosis and inflammation, 2 had hepatic thrombophlebitis, and 1 had tracheal occlusion. These lesions were associated with migrating nematode larvae morphologically consistent with T. canis . The identity of the larvae was confirmed by sequencing of a portion of the ITS-2 region of nuclear ribosomal DNA. The tissues involved are consistent with the known migration pathways of this parasite. The dam of the first litter was negative for Toxocara spp . and other intestinal parasites by fecal floatation. This report highlights the need to consider T. canis migration in the differential diagnosis of fading puppies.